Sustainable Coastal Land Management in Serdang Bedagai - Saifullah Saifullah; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Coastal areas are vital for ecosystems, social, and economic systems, yet they face challenges like erosion, land-use conversion, and weak community-based management. Serdang Bedagai Regency, located in North Sumatra, has significant ecological and socio-cultural potential, but this potential has not been sustainably managed. This study analyzes strategies for sustainable coastal land management by integrating local wisdom and village government roles. A mixed-method approach was used, including in-depth interviews, field observations, and surveys with 30 respondents from two coastal villages. The qualitative findings reveal that traditional practices, such as prohibiting mangrove cutting and communal conservation traditions, are still alive in the community. The village government plays a crucial role in strengthening institutions through village regulations (Perdes), environmental programs, and spatial monitoring. However, there is a gap between community understanding of ecological values and the implementation of regulations. Quantitative analysis using multiple linear regression shows that both local wisdom and the village government's role significantly influence sustainable coastal land management, with coefficients of 0.491 and 0.426, respectively (p < 0.05). Despite some heteroskedasticity, the model passed tests for multicollinearity and normality. These findings highlight the importance of combining traditional values with institutional support to balance coastal resource utilization and conservation. This study contributes to the development of a socio-ecological coastal governance model and offers practical recommendations for village governments, policymakers, and academics in creating participatory and sustainable coastal preservation programs.